Analysis of International Trade between Indonesia with ASEAN-8 - Pisi Bethania Titalessy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
International trade is one of way to increase foreign exchange of a country. AEC is a form of economic integration of ASEAN in terms of a system of free trade between ASEAN countries. Because there is free trade system, Indonesia should prepare to face the AEC. This study aimed to analyze the factors that affect international trade by looking at the effect of variables Gross Domestic Product (GDP), Foreign Direct Investment (FDI), the distance between exporters and importers, and the population towards total exports. Analyses were performed using panel data regression to know the influence that occurs between the independent variables and the dependent. From the results of the panel data regression is known that variables of GDP of importer country, FDI of importer country, and the total population of the importer country has a positive and significant impact on Indonesia's total exports. Meanwhile, the variable distance between the exporter and importer countries showed a negative influence on bilateral trade in ASEAN.Keywords: GDP, FDI, Distance, Population